Evaluation of the Role of an Extract of A Group of Medicinal Plants with Honey and Vitamin B (Energy Fort Supplement) In Improving some Physiological Responses of Purebred Arabian Horses Before and After the Race (Journal of Hama University, 2024)
This research was conducted to study the physiological responses in purebred Arabian horses by knowing the biochemical changes in the level of glucose and lactate before and after the 1600-meter race and knowing the effect of medicinal extracts of Ginseng, Phyllanthus, Saussurea Costus, Alpinia, Celery and Mustard Seeds, in addition to the vitamin B group and honey included in the Energy Fort preparation, in improving of Physiological responses and alleviation of some of the effects of post-race muscle fatigue.The horses were distributed into five groups, each group included six horses with similar weights according to the following:-The First Group (G1): the normal control group. The horses were left without any race or exercise, to know the normal values of the studied variables (Glucose, Lactate). -The Second Group (G2): The horses underwent a 1,600-meter gallop, then blood samples were collected from them immediately after the race, as this group was considered a positive control for The Third Group.-The Third Group (G3): The horses in this group were given an Energy Fort supplement at a dose of 2 ml / 100 kg of body weight immediately before the 1600-meter race, and then blood samples were collected from them immediately after the race.-The Fourth Group (G4): The horses underwent a 1,600-meter gallop, then blood samples were collected from them immediately after the race, as this group was considered a positive control for The Fifth Group.-The Fifth Group (G5): The horses in this group underwent a 1,600-meter gallop, then were given Energy Fort supplement at a dose of 2 ml/100 kg body weight immediately after the race, and half an hour after giving the supplement, blood samples were collected from this group.All blood samples were obtained from the Jugular Vein.The results showed that real changes occurred in the physiological responses, represented by a significant increase in the average concentrations of Lactate and Glucose after the race in the positive control groups (G4-G2) when compared with the group of the normal control (G1), and a significant decrease in the average concentrations of lactate and glucose after the race in the groups Race (G5-G3) given Energy Fort supplement before and after race when compared with a positive control group (G2-G4)
Keywords: : Physiological Responses, Glucose, Lactate, Acidosis, Lactate Shuttle, Physiological Adaptations, Physical Fitness, Purebred Arabian Horses